2022
DOI: 10.3389/fonc.2021.817781
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Urine Is Associated With Poor Prognosis of Upper Tract Urothelial Carcinoma

Abstract: PurposeTo assess the prognostic role of acidic urine (low urine pH) in upper tract urothelial cancer (UTUC).Materials and MethodsWe reviewed patients enrolled in Seoul National University Prospectively Enrolled Registry for Urothelial Cancer-Upper Tract Urothelial Cancer (SUPER-UC-UTUC) who underwent surgical resection from March 2016 to December 2020 in Seoul National University Hospital (SNUH). Patients with non-urothelial cancer or those who are in condition at end-stage renal disease were excluded. Acidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Han et al . 25 has demonstrated that multifocal tumors, acidic urine pH, and advanced T-stage independently shorten recurrence-free survival. A study conducted by Wright et al .…”
Section: Discussionmentioning
confidence: 99%
“…Han et al . 25 has demonstrated that multifocal tumors, acidic urine pH, and advanced T-stage independently shorten recurrence-free survival. A study conducted by Wright et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, acidic urine has been found to be common in patients with sarcopenia ( 12 ), coronary artery disease ( 13 ), DM ( 14 ), and metabolic syndrome ( 15 ). In investigations related to nephro-urology, acidic urine was reported to increase the risk of chronic renal failure and urolithiasis ( 16 , 17 ), and may also be associated with poor prognosis in urothelial carcinoma patients ( 18 ). On the other hand, alkaline urine is commonly found in urinary tract infection cases and often promotes formation of infected urolithiasis.…”
Section: Discussionmentioning
confidence: 99%